Ganglioside GM2: a potential biomarker for cholangiocarcinoma. Issue 7 (July 2020) - Talabnin, Krajang; Talabnin, Chutima; Kumagai, Tadahiro; Sutatum, Nuchanard; Khiaowichit, Juthamas; Dechsukhum, Chawaboon; Ishihara, Mayumi; Azadi, Parastoo; Sripa, Banchob
Objective: To investigate the expression of glycosphingolipids in serum and tissue from patients with cholangiocarcinoma compared with healthy controls. Methods: Nanospray ionization-linear ion trap mass spectrometry (NSI-MS n ) was used to demonstrate the comparative structural glycomics of glycosphingolipids in serum from patients with cholangiocarcinoma (n=15), compared with healthy controls (n = 15). GM2 expression in cholangiocarcinoma tissues (n = 60) was evaluated by immunohistochemistry. Results: Eleven glycosphingolipids were detected by NSI-MS n : CMH (ceramide monohexose), Lac-Cer (galactose (Gal)β1-4 glucose (Glc)β1-1'-ceramide), Gb3 (Galα1-4Galβ1-4Glcβ1-1'-ceramide), Gb4/Lc4 (N-acetylgalactosamine (GalNAc)β1-3Galα1-4Galβ1-4Glcβ1-1'-ceramide/Galβ1-4 N-acetylglucosamine (GlcNAc)β1-3Galβ1-4Glcβ1-1'-ceramide), GM3 (N-acetylneuraminic acid (NeuAc)2-3Galβ1-4Glcβ1-1'-ceramide), GM2 (GalNAcβ1-4[NeuAc2-3]Galβ1-4Glcβ1-1'-ceramide), GM1 (Galβ1-3GalNAcβ1-4[NeuAc2-3]Galβ1-4Glcβ1-1'-ceramide), hFA (hydroxylated fatty acid)-CMH, hFA-Lac-Cer, hFA-Gb3, and hFA-GM3. Lac-Cer was the most abundant structure among the lactosides and globosides (normal, 24.40% ± 0.11%; tumor, 24.61% ± 2.10%), while GM3 predominated among the gangliosides (normal, 29.14% ± 1.31%; tumor, 30.53% ± 4.04%). The two glycosphingolipids that significantly differed between healthy controls and patients with cholangiocarcinoma were Gb3 and GM2. High expression of GM2 was associated with vascular invasion in tissue from patients with cholangiocarcinoma. Conclusions: Altered expression of glycosphingolipids in tissue and serum from patients with cholangiocarcinoma may contribute to tumor growth and progression. The ganglioside GM2, which significantly increased in the serum of patients with cholangiocarcinoma, represents a promising target as a biomarker for cholangiocarcinoma.